Analysis of Time and Cost Control in a 2-Storey Construction Project Using the Earned Value Method (Case Study: Puri Cempaka Serang Housing Development Project) - Setiawati, Dwi Novi; P, Bambang Setyo; Kurniawan, Inggit (Jurnal Fondasi, 2023)
Poor planning is a common factor in project delays. For this reason, a time and cost analysis method is needed which can examine how much deviation occurs and the remaining time and costs to complete the project. The purpose of this research is to find out time and cost performance, what causes delays, and the estimated time and cost of project completion. For management activities costs (Cost Management) and time management (Time Management) can be This is done by using one of the project control methods, namely the value concept method results (Earned Value). The Earned Value (EV) method is one of the techniques for determining the real advantages and disadvantages of projects and provides a means to balance gains/losses and maximize profits. Week 1 to week 9 cost performance saves job fees. However, from the 14th to the 20th week of experiencing expenditure is greater than the project budget with a CPI value of 0,748 and performance The time from week 1 to week 9 is faster. But from week 13 to week, 20 time performance is slower with an SPI value of 0,59. The result of the calculation of the estimated cost of completing the project is Rp. 5.245.556.910 with an estimated turnaround time of 41 weeks, showing the project was 17 weeks late from the planned 24 weeks. Causative factor delays are work drawings or shop drawings that are late coming out as well as their gradual submission, lack of fill land, and workers getting a portion of the Eid holiday of ± 1 month.